Analisis Sifat Mekanik dan Topografi Permukaan Bata Merah di Kabupaten Bangka dengan Menggunakan Metode RSM - Yuliyanto Yuliyanto; Eko Yudo; Zakdi Sirwansyah Suzen (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2019)
The use of bricks in both non-structural and structural construction needs to be an increase in the product produced, either by improving the quality of materials based on SNI 15-2094-2000 which explains the red brick. The purpose of this study was to analyze the effect of the Independent Variable, namely the Comparison of heating temperatures with a processing time of 12 hours, 24 hours and 36 hours, with temperatures of 300oC, 500oC and 700oC and the percentage of sand mixture of 5%, 10% and 15%. Comparison of the three independent variables will be seen what is the Optimum value of the Impact test and how the fracture that occurs is seen with SEM. The results show the smallest impact value of 264 kj / m2, and the largest value of 164 kj / m2. the calculated F value of FModel = 33.29 obtained at a significant level of 0.01 or 1% and the p value (0.0002) gives a significant value to the existing model. Whereas the Lack of Fit that occurs is 0.000199 and does not have an effect (not significant) so that the cubic mathematical model regression equation used can be accepted. Based on the interaction data and surface response to the impact strength, the effect of heating time, heating temperature and percentage of sand is very large. The point is that if the temperature and the heating time get bigger the impact test results will be even greater